Gulf Cooperation Council monetary unification - Alyafai, Yahya (Kansas State University, 2011)
In this report, I investigate the possibility of a monetary unification among the Arab States. The Gulf Cooperation Council (GCC) states that include Bahrain, Saudi Arabia, Qatar, UAE, Kuwait and Oman are coming together on the basis of common ethnicity, religion, culture, traditions, and monetary issues. This research will discuss different factors upon which the monetary unification and the birth of a new currency depend. For comparison to the Euro, I closely examined different factors such as inflation rates, exchange rates, trade, etc. over the past decade. As stated, this examination was done to see how these factors compare with those of the Euro region to determine if a similar monetary unification among the GCC states is possible. The target date for launching the new GCC currency was January 1, 2010; however that date has long passed. Although the above mentioned factors are favorable to currency unification of the GCC states, ample time is necessary to achieve such a herculean feat. After all, the Europeans did not achieve the unification of the Euro in one night. One hurdle to unification is that the GCC states still need to control the inflation rates in their own economies. Other economic factors, such as trade, have been favorable for all the GCC states, and all the states have been doing well in terms of the U.S. dollar (USD). Although unification may not have met the January 1, 2010 goal, the GCC will still be observing the economic factors and considering other possible scenarios. All the GCC countries vow to achieve this unification.
Keywords: GCC; Monetary union; Economics (0501)